Pelatihan Manajemen Bank Sampah Guna Pelestarian Lingkungan dan Meningkatkan Nilai Ekonomis Masyarakat Di Kecamatan Namorambe Kabupaten Deliserdang - Tomy Sun Siagian; Darmawan Sriyanto; Muhammad Andi Rasyid; Dhea Agusty Ningrum; Rulli Yani (Universitas Islam Negeri Sumatera Utara, 2022)
AbstractAlong with the incrase population density especially in Deli Serdang, it can’t be separated from the incrase amount of waste. The garbage will incrase with population too, this isi so importance to solve. The result from Environmental Service of Deli Serdang there was 1.078 tons/day the waste production in Deli Serdang. Most of the waste produced from household and the rest comes from companies, offices, school, and others. To solved this problems it is necessary socialitation to public for managing their waste. If garbage managed properly it will be have a positive impact through composting and economic value added from a waste bank. The schools are the place that having the important role of social values to students, so they can think that they have to get knowledge about wasting management. From This PKM we expected the schools can get the knowledge about waste management methods that will be useful in society. This PKM activity is a workshop to teachers and students especially about waste management. The output of the implementation from this activity is all of society in the school getting the knowledge and skill in waste management.